Porous silicon carbon negative electrode material and preparation method and application thereof
By setting a conductive carbon rod and a conductive carbon layer in the porous silicon carbon anode material to form a spatial three-dimensional network conductive channel structure, the problem of poor conductivity of the existing porous silicon carbon anode material is solved, and the battery's magnification and voltage platform performance is significantly improved.
Patent Information
- Application Number
- CN202411727945.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The current porous silicon carbon anode materials have poor electrical conductivity, which affects the battery's magnification and voltage platform performance.
By installing conductive carbon rods inside the porous silicon carbon and forming them with the conductive carbon layer on the surface, a spatial three-dimensional network conductive channel structure is formed to improve the conductive properties of the material.
It significantly improves the conductivity of porous silicon carbon anode material, reduces the resistance of the negative electrode sheet diaphragm of the whole battery, and improves the rate performance of the whole battery.
Smart Images

Figure CN119560528A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and relates to a negative electrode of a secondary battery, and in particular to a porous silicon-carbon negative electrode material, a preparation method and an application thereof. Background Art
[0002] As the third-generation silicon-based negative electrode material, porous silicon carbon is based on the principle of nano-silicon being deposited on a porous carbon skeleton. Compared with the first-generation silicon negative electrode (silicon oxygen negative electrode) and the second-generation silicon negative electrode (pre-lithiation silicon oxygen), it takes into account high capacity and high initial efficiency (the first-generation silicon oxygen has a low initial efficiency), while ensuring a low expansion rate of the negative electrode (the expansion rate of the negative electrode of the first and second-generation silicon oxygen is relatively large), and is the best product for silicon negative electrode in the future. However, silicon negative electrode materials have always had the problem of poor conductivity compared to graphite materials. The third-generation silicon series (porous silicon carbon) currently on the market is far inferior to graphite negative electrode in terms of material conductivity. After being made into finished batteries, it has a great impact on the overall rate and voltage platform of the battery. In response to this problem, the carbon skeleton of the third-generation silicon carbon and the vapor phase precipitation of nano-silicon have been improved for many rounds, such as adding conductive materials with strong conductivity to the carbon source for generating the carbon skeleton, or improving the deposition of nano-silicon, but the effects are not very significant. Summary of the invention
[0003] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a porous silicon-carbon negative electrode material and a preparation method and application thereof. The porous silicon-carbon negative electrode material provided by the present invention has a spatial three-dimensional network conductive channel structure, which can significantly improve the conductive properties of the porous silicon-carbon negative electrode material, greatly reduce the diaphragm resistance of the negative electrode of the whole battery, and at the same time improve the rate performance of the whole battery.
[0004] In order to achieve the above object, the technical solution of the present invention is:
[0005] In a first aspect, a porous silicon-carbon negative electrode material comprises porous silicon-carbon, wherein the porous silicon-carbon is a porous carbon matrix and nano-silicon deposited in the porous carbon matrix, the surface of the porous silicon-carbon is coated with a conductive carbon layer, a plurality of space channels are arranged in the porous silicon-carbon, the space channels are filled with conductive carbon to form conductive carbon rods, and the conductive carbon rods and the conductive carbon layer are integrally formed into a spatial three-dimensional network conductive channel structure.
[0006] The present invention arranges conductive carbon rods inside the porous silicon carbon and forms an integral structure with the conductive carbon layer on the surface of the porous silicon carbon to form a spatial three-dimensional network conductive channel structure, so that the material not only improves the conductive performance of the particle surface, but also improves the conductive performance of the particle interior, thereby significantly improving the conductive performance of the porous silicon carbon negative electrode material.
[0007] In a second aspect, a method for preparing a porous silicon-carbon negative electrode material comprises the following steps:
[0008] The first carbon source, the second carbon source and the inorganic salt are used to prepare a porous carbon matrix containing the inorganic salt;
[0009] Using a silicon source to deposit nano-silicon on the porous carbon matrix to obtain a nano-silicon deposited carbon matrix;
[0010] The nano-silicon deposited carbon matrix is subjected to heat treatment to decompose and volatilize the internal inorganic salt, and the volatilized gas forms a space channel extending from the surface to the interior in the nano-silicon deposited carbon matrix;
[0011] acid washing the heat-treated nano-silicon deposited carbon substrate;
[0012] Using gaseous hydrocarbon as the deposited carbon source, the acid-washed nano-silicon deposited carbon matrix is subjected to vapor phase carbon deposition, so that the deposited carbon fills the space channels in the nano-silicon deposited carbon matrix to form conductive carbon rods, and at the same time, the deposited carbon is deposited on the surface of the nano-silicon deposited carbon matrix to form a conductive carbon layer.
[0013] The above-mentioned preparation method of the present invention, when preparing a porous carbon matrix, incorporates an inorganic salt into the porous carbon matrix, first deposits nanosilicon to fill the surface and pores of the porous carbon matrix, and then performs heat treatment so that the inorganic salt pyrolysis can form a spatial channel extending from the surface to the inside in the nanosilicon deposited carbon matrix, and then performs gas phase carbon deposition after acid washing to remove metal impurities, so that the deposited carbon can simultaneously fill the spatial channel and be coated on the surface of the nanosilicon deposited carbon matrix, thereby forming a spatial three-dimensional network conductive channel structure in one piece, and the conductive performance of the porous silicon-carbon negative electrode material can be significantly improved through this structure. At the same time, the present invention first deposits nanosilicon and then pyrolyzes the inorganic salt, which can avoid the problem of later depositing nanosilicon to fill the spatial channel, causing the spatial channel to be blocked and unable to form a spatial three-dimensional network conductive channel structure.
[0014] In addition, the present invention uses gaseous hydrocarbons as a deposited carbon source for gas phase carbon deposition (i.e., chemical vapor deposition), which can make the prepared deposited carbon have a layered structure and the carbon atoms in the layer are connected by covalent bonds, that is, the deposited carbon is graphite, which has good electrical conductivity, thereby giving the spatial three-dimensional network conductive channel structure conductivity.
[0015] In a third aspect, an application of the above-mentioned porous silicon-carbon negative electrode material in the preparation of negative electrode sheets.
[0016] In a fourth aspect, a secondary battery includes a positive electrode, a negative electrode and an electrolyte, wherein the active material used in the negative electrode includes the above-mentioned porous silicon-carbon negative electrode material.
[0017] The beneficial effects of the present invention are:
[0018] The present invention adds an inorganic salt that can decompose and produce gas at high temperature to the raw materials for making the porous carbon matrix. The inorganic salt decomposes and produces gas in the subsequent heat treatment after the nano-silicon is deposited. The gas generated by the inorganic salt volatilizes in the nano-silicon deposited carbon matrix to produce a gasification space channel. The generated gasification space channel will be covered by the carbon deposition coating in the subsequent carbon deposition coating (because the carbon deposition coating has better conductivity than the porous carbon skeleton) to form a spatial three-dimensional network of conductive channels. Compared with the conventional vapor-deposited silicon carbon on the market, whose carbon coating is only attached to the surface of nano-silicon and carbon matrix, the spatial three-dimensional network conductive channel of the porous silicon-carbon negative electrode material of the present invention greatly improves the powder conductivity of the material, while improving its full battery negative electrode sheet diaphragm resistance and full battery rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] Figure 1 The schematic diagram of the structure of the porous carbon matrix prepared in the process of preparing the porous silicon-carbon negative electrode material of the present invention is as follows: 1. The porous carbon matrix;
[0021] Figure 2 The schematic diagram of the structure of the nano-silicon deposited carbon matrix prepared in the process of preparing the porous silicon-carbon negative electrode material of the present invention, 1. porous carbon matrix, 2. nano-silicon;
[0022] Figure 3 This is a schematic diagram of the structure of the nano-silicon deposited carbon matrix after heat treatment in the preparation process of the porous silicon-carbon negative electrode material of the present invention, 1. porous carbon matrix, 2. nano-silicon, 3. space channel;
[0023] Figure 4 Schematic diagram of the structure of the porous silicon-carbon negative electrode material prepared by the present invention, 1. porous carbon matrix, 2. nano-silicon, 3. space channel, 4. conductive carbon layer;
[0024] Figure 5 This is a scanning electron microscope (SEM) image of the porous silicon-carbon negative electrode material prepared in Example 1 of the present invention;
[0025] Figure 6 This is a cross-sectional SEM image of the porous silicon-carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0027] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0028] In order to better solve the problem of poor electrical conductivity of existing porous silicon carbon, the present invention proposes a porous silicon carbon negative electrode material and a preparation method and application thereof.
[0029] A typical embodiment of the present invention provides a porous silicon-carbon negative electrode material, including porous silicon-carbon, wherein the porous silicon-carbon is a porous carbon matrix and nano-silicon deposited in the porous carbon matrix, the surface of the porous silicon-carbon is covered with a conductive carbon layer, a plurality of spatial channels are arranged in the porous silicon-carbon, the spatial channels are filled with conductive carbon to form conductive carbon rods, and the conductive carbon rods and the conductive carbon layer are integrally formed into a spatial three-dimensional network conductive channel structure.
[0030] In some embodiments, the mass of the nano-silicon is 20-70% of the mass of the porous silicon carbon.
[0031] In some embodiments, the mass of the spatial three-dimensional network conductive channel structure is 1.0 to 5.0% of the total mass of the porous silicon-carbon negative electrode material, preferably 1.0 to 2.0%, and more preferably 1.2 to 1.5%.
[0032] Another embodiment of the present invention provides a method for preparing a porous silicon-carbon negative electrode material, comprising the following steps:
[0033] The first carbon source, the second carbon source and the inorganic salt are prepared into a porous carbon matrix 1 containing an inorganic salt, such as Figure 1 As shown;
[0034] A silicon source is used to deposit nano-silicon on the porous carbon matrix 1, so that the nano-silicon 2 is filled into the pores of the porous carbon matrix 1, and a nano-silicon deposited carbon matrix is obtained, such as Figure 2 As shown;
[0035] The nano-silicon deposited carbon matrix is subjected to heat treatment to decompose and volatilize the internal inorganic salt, and the volatilized gas forms a space channel 3 extending from the surface to the interior in the nano-silicon deposited carbon matrix, such as Figure 3 As shown;
[0036] acid washing the heat-treated nano-silicon deposited carbon substrate;
[0037] Using gaseous hydrocarbon as a deposited carbon source, the pickled nano-silicon deposited carbon matrix is subjected to gas phase carbon deposition, so that the deposited carbon fills the space channel 3 in the nano-silicon deposited carbon matrix to form a conductive carbon rod, and at the same time, the deposited carbon is deposited on the surface of the nano-silicon deposited carbon matrix to form a conductive carbon layer 4, such as Figure 4 As shown, the conductive carbon rods and the conductive carbon layer 4 are integrally formed into a spatial three-dimensional network conductive channel structure through vapor phase carbon deposition.
[0038] In some embodiments, the first carbon source is selected from one or more of phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, silicone resin, polyester resin, polyamide resin, polytetrafluoroethylene, acrylic resin, glucose, and sucrose. The first carbon source contains a large amount of carbon, hydrogen, oxygen, fluorine and other elements, which can be cracked into gas during the carbonization process, so that the prepared carbon material has a porous structure.
[0039] In some embodiments, the second carbon source is selected from at least one of polyvinylidene fluoride, polyethylene, polypropylene, polymethylstyrene, and styrene-butadiene rubber.
[0040] The inorganic salt described in the present invention is a compound that can be pyrolyzed to generate gas. In some embodiments, the inorganic salt is calcium carbonate or copper sulfate.
[0041] In some embodiments, the mass ratio of the first carbon source, the second carbon source, and the inorganic salt is 90-95:0.2-5:1-10.
[0042] In some embodiments, the process of preparing the porous carbon matrix is: mixing the first carbon source, the second carbon source and the inorganic salt to form a granular material, and then sintering the granular material under inert atmosphere conditions. Specifically, the granulation temperature is 150 to 250° C., under which the granular material is formed. Specifically, the sintering temperature is 300 to 500° C., preferably 440 to 460° C. Specifically, the sintering time is 1 to 3 hours.
[0043] In some embodiments, the particle size D of the porous carbon matrix is 50 3~15μm.
[0044] In some embodiments, the silicon source is selected from at least one of monosilane, disilane, trisilane, dichlorodihydrogensilane, trichlorosilane, trichlorosilane chlorosilane, and silicon tetrachloride.
[0045] In some embodiments, the process of nano-silicon deposition is: mixing a silicon source with an inert gas and performing vapor deposition at 300-600° C. Specifically, the inert gas is selected from at least one of argon, neon, helium and nitrogen. Specifically, the temperature of the vapor deposition is 430-470° C.
[0046] In some embodiments, in the nano-silicon deposited carbon matrix, the nano-silicon pore filling deposition rate is 35-90%, preferably 75-85%, and more preferably 78-82%, and the pore volume is 0.05-0.80 cm 3 / g, and the weight proportion of nano silicon is 20-70%.
[0047] In some embodiments, the temperature of the heat treatment is 650-1000° C. In order to better form the spatial channel, the heat treatment is performed under vacuum conditions. Specifically, the heat treatment time is 2-5 hours.
[0048] In some embodiments, the acid mass concentration used in pickling is 1 to 15 wt %. Under this condition, the metal elements can be better removed. Drying is performed after pickling. Specifically, the drying temperature is 80 to 100° C. and the drying time is 1 to 3 hours. Specifically, the drying is vacuum drying.
[0049] In some embodiments, the gaseous hydrocarbon is selected from methane, ethylene, acetylene, propane, and propylene.
[0050] In some embodiments, the temperature of the vapor phase carbon deposition is 400-900° C., and the time of the vapor phase carbon deposition is 1-3 hours.
[0051] In some embodiments, the mass of carbon deposited by vapor phase carbon is 1-5% of the total mass of the final product.
[0052] A third embodiment of the present invention provides a use of the above-mentioned porous silicon-carbon negative electrode material in the preparation of a negative electrode sheet.
[0053] Specifically, the negative electrode sheet is composed of a current collector and an active layer attached to the surface of the current collector, and the active material in the active layer includes the porous silicon-carbon negative electrode material. More specifically, the active material, the conductive agent, the binder, and the thickener are added to a solvent to form a slurry, and the slurry is placed on the surface of the current collector and dried to obtain. More specifically, the active material also includes graphite. The mass ratio of graphite to the porous silicon-carbon negative electrode material is 15.0 to 20.0:1, preferably 18.0 to 19.0:1.
[0054] A fourth embodiment of the present invention provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the active material used in the negative electrode comprises the above-mentioned porous silicon-carbon negative electrode material.
[0055] The secondary battery described in the present invention refers to a rechargeable battery or a storage battery, which can be classified by electrolyte form and can be a liquid battery, a semi-solid battery, a solid battery, etc.; classified by chemical composition, it can be a lithium ion battery, a sodium ion battery, a zinc ion battery, a magnesium ion battery, an aluminum ion battery, a lead-acid battery, a nickel-cadmium battery, a nickel-hydrogen battery, etc.
[0056] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0057] Embodiment 1:
[0058] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0059] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0060] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0061] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0062] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0063] (5) The nano-silicon deposited carbon substrate after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700° C., the vapor phase carbon deposition time is 2 h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, to obtain a porous silicon-carbon negative electrode material, such as Figures 5-6 shown.
[0064] Embodiment 2:
[0065] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0066] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, copper sulfate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200°C to obtain a granular material, and then the granular material is heated to 450°C in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50The porous carbon matrix is 8 μm.
[0067] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0068] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0069] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0070] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0071] Embodiment 3:
[0072] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0073] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 400° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 6 μm.
[0074] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0075] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0076] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0077] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0078] Embodiment 4:
[0079] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0080] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 400° C. in an argon atmosphere and sintered for 2.5 hours to obtain a particle size D 50 The porous carbon matrix is 7 μm.
[0081] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0082] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0083] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0084] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0085] Embodiment 5:
[0086] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0087] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0088] (2) Using disilane as a silicon source, the silicon source and argon gas are vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0089] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0090] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0091] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0092] Embodiment 6:
[0093] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0094] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0095] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 550° C. for 2.5 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 75% and the pore volume is 0.55 cm 3 / g, and nano-silicon accounts for 35% by weight.
[0096] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0097] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0098] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0099] Embodiment 7:
[0100] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0101] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0102] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0103] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0104] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0105] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from ethylene, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0106] Embodiment 8:
[0107] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0108] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0109] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0110] (3) The nano-silicon deposited carbon substrate obtained in step (2) is heated to 900° C. under vacuum conditions for 3 hours.
[0111] (4) The nano-silicon deposited carbon substrate after the heat treatment in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0112] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 1.8h, and the mass of the vapor phase carbon deposition accounts for 1.2% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0113] Comparative Example 1:
[0114] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0115] (1) Phenolic resin is selected as the first carbon source and polyethylene is selected as the second carbon source. The mass ratio of the first carbon source to the second carbon source is 90:10, and the mixture is uniformly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material. The granular material is then heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0116] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0117] (3) The nano-silicon deposited carbon substrate obtained in step (2) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0118] (4) The nano-silicon deposited carbon matrix after acid washing and drying in step (3) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0119] Comparative Example 2:
[0120] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0121] (1) Phenolic resin is selected as the first carbon source and polyethylene is selected as the second carbon source. The mass ratio of the first carbon source to the second carbon source is 90:8, and the mixture is uniformly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material. The granular material is then heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0122] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0123] (3) The nano-silicon deposited carbon substrate obtained in step (2) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0124] (4) The nano-silicon deposited carbon matrix after acid washing and drying in step (3) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0125] Comparative Example 3:
[0126] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0127] (1) Phenolic resin is selected as the first carbon source and polyethylene is selected as the second carbon source. The mass ratio of the first carbon source to the second carbon source is 90:10, and the mixture is uniformly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material. The granular material is then heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0128] (2) Using monosilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the porous carbon substrate obtained in step (1) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0129] (3) The nano-silicon deposited carbon substrate obtained in step (2) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0130] (4) The nano-silicon deposited carbon matrix after acid washing and drying in step (3) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 1.8h, and the mass of the vapor phase carbon deposition accounts for 1.2% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0131] Comparative Example 4:
[0132] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0133] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0134] (2) The porous carbon substrate obtained in step (1) is heated to 900° C. under vacuum conditions and heat treated for 3 hours.
[0135] (3) Using monosilane as a silicon source, the silicon source and argon gas are vapor-deposited on the heat-treated porous carbon substrate obtained in step (2) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0136] (4) The nano-silicon deposited carbon substrate obtained in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0137] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0138] Comparative Example 5:
[0139] A method for preparing a porous silicon-carbon negative electrode material, the steps are as follows:
[0140] (1) Phenolic resin is selected as the first carbon source, polyethylene is selected as the second carbon source, and the mass ratio of the first carbon source, calcium carbonate, and the second carbon source is 90:2:8, and the mixture is evenly mixed to obtain a mixed material. The mixed material is stirred and granulated at 200° C. to obtain a granular material, and then the granular material is heated to 450° C. in an argon atmosphere and sintered for 2 hours to obtain a particle size D 50 The porous carbon matrix is 8 μm.
[0141] (2) The porous carbon substrate obtained in step (1) is heated to 900° C. under vacuum conditions and heat treated for 3 hours.
[0142] (3) Using disilane as a silicon source, the silicon source and argon gas are mixed in a volume ratio of 1:1, and vapor-deposited on the heat-treated porous carbon substrate obtained in step (2) at a temperature of 500° C. for 3 h to obtain a nano-silicon deposited carbon substrate, wherein the nano-silicon pore filling deposition rate is 80% and the pore volume is 0.5 cm 3 / g, and nano-silicon accounts for 40% by weight.
[0143] (4) The nano-silicon deposited carbon substrate obtained in step (3) is pickled with 3 wt % hydrochloric acid, and then vacuum dried at 100° C. for 3 h.
[0144] (5) The nano-silicon deposited carbon matrix after acid washing and drying in step (4) is coated with vapor phase carbon deposition, the carbon source is selected from methane, the vapor phase carbon deposition temperature is 700°C, the vapor phase carbon deposition time is 2h, and the mass of the vapor phase carbon deposition accounts for 1.5% of the mass of the final product, thereby obtaining a porous silicon-carbon negative electrode material.
[0145] The silicon negative electrodes obtained in all the above embodiments and comparative examples are made into soft-pack full cells. The soft-pack cell production process is as follows:
[0146] Make 5Ah ternary soft-pack full battery cells;
[0147] Full battery production: The positive electrode active material is NCM622 polycrystalline material, and the positive electrode formula is PVDF:SP:CNT:NCM=2%:1.5%:0.5%:96%. The positive electrode surface density is 200±3g / m 2 , cold pressed to 2.4g / m 3 , after punching and cutting, the positive electrode sheet is obtained;
[0148] The negative electrode active material is a composite of graphite (Gr) and the porous silicon-carbon negative electrode material (denoted as Si / C) prepared above, and the negative electrode formula is SBR:SP:CMC:Gr:Si / C=1.8%:1%:1.2%:91%:5%. The negative electrode surface density is 98±3g / m 2 , cold pressed to 1.60g / m 3 , and the negative electrode sheet is obtained after punching.
[0149] The diaphragm is a (9+3+2) μm wet-process single-sided glue-coated diaphragm (wherein the PE base film is 9 μm, the glue layer is 3 μm, and the ceramic layer is 2 μm), the electrolyte is LiPF6:EC:EMC:DMC:VC:LiODFB:PS=12:40:30:12:1.5:2:2.5, and the injection coefficient is 2.6. The resistance of the silicon negative electrode powder obtained by the embodiment and the comparative example is compared:
[0150] Group Powder resistivity Ω·m Group Powder resistivity Ω·m Example 1 1.12 Example 8 1.16 Example 2 1.15 Comparative Example 1 3.52 Example 3 1.11 Comparative Example 2 3.68 Example 4 1.05 Comparative Example 3 3.56 Example 5 1.18 Comparative Example 4 3.47 Example 6 1.20 Comparative Example 5 3.46 Example 7 1.15 / /
[0151] The performance of the negative electrode sheet made of the silicon negative electrode obtained in the embodiment and the comparative example is compared:
[0152] Group Electrode sheet resistance (mΩ) Group Electrode sheet resistance (mΩ) Example 1 0.67 Example 8 0.65 Example 2 0.72 Comparative Example 1 1.21 Example 3 0.71 Comparative Example 2 1.22 Example 4 0.72 Comparative Example 3 1.20 Example 5 0.68 Comparative Example 4 1.18 Example 6 0.66 Comparative Example 5 1.19 Example 7 0.68 / /
[0153] The performance of the full battery made of the silicon negative electrode obtained in the embodiment and the comparative example is compared (national standard GB31486):
[0154]
[0155]
[0156] From the comparison between the embodiment and the comparative example, it can be seen that the conductive property of the porous silicon-carbon negative electrode material prepared by the present invention is greatly improved compared with the porous silicon-carbon negative electrode material prepared by the conventional process.
[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A porous silicon-carbon negative electrode material, characterized in that: The porous silicon carbon comprises a porous carbon matrix and nano-silicon deposited in the porous carbon matrix. The surface of the porous silicon carbon is coated with a conductive carbon layer. A plurality of space channels are arranged in the porous silicon carbon. The space channels are filled with conductive carbon to form conductive carbon rods. The conductive carbon rods and the conductive carbon layer are integrally formed into a spatial three-dimensional network conductive channel structure.
2. The porous silicon-carbon negative electrode material according to claim 1, characterized in that: The mass of nano silicon is 20-70% of the mass of the porous silicon carbon; Alternatively, the mass of the spatial three-dimensional network conductive channel structure is 1.0 to 5.0% of the total mass of the porous silicon-carbon negative electrode material, preferably 1.0 to 2.0%, and more preferably 1.2 to 1.5%.
3. A method for preparing a porous silicon-carbon negative electrode material, characterized in that: The steps include: The first carbon source, the second carbon source and the inorganic salt are used to prepare a porous carbon matrix containing the inorganic salt; Depositing nano-silicon on the porous carbon matrix using a silicon source, so that the nano-silicon is filled into the pores of the porous carbon matrix, thereby obtaining a nano-silicon deposited carbon matrix; The nano-silicon deposited carbon matrix is subjected to heat treatment to decompose and volatilize the internal inorganic salt, and the volatilized gas forms a space channel extending from the surface to the interior in the nano-silicon deposited carbon matrix; acid washing the heat-treated nano-silicon deposited carbon substrate; Using gaseous hydrocarbon as the deposited carbon source, the acid-washed nano-silicon deposited carbon matrix is subjected to vapor phase carbon deposition, so that the deposited carbon fills the space channels in the nano-silicon deposited carbon matrix to form conductive carbon rods, and at the same time, the deposited carbon is deposited on the surface of the nano-silicon deposited carbon matrix to form a conductive carbon layer.
4. The method for preparing the porous silicon-carbon negative electrode material according to claim 3, characterized in that: The first carbon source is selected from one or more of phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, silicone resin, polyester resin, polyamide resin, polytetrafluoroethylene, acrylic resin, glucose, and sucrose; Or, the second carbon source is selected from at least one of polyvinylidene fluoride, polyethylene, polypropylene, polymethylstyrene, and styrene-butadiene rubber; Or, the inorganic salt is calcium carbonate or copper sulfate; Or, the silicon source is selected from at least one of monosilane, disilane, trisilane, dichlorodihydrogensilane, trichlorosilane, trichlorosilane chlorosilane and silicon tetrachloride; Alternatively, the gaseous hydrocarbon is selected from methane, ethylene, acetylene, propane, and propylene.
5. The method for preparing the porous silicon-carbon negative electrode material according to claim 3, characterized in that: The mass ratio of the first carbon source, the second carbon source and the inorganic salt is 90-95:0.2-5:1-10; Or, the particle size D of the porous carbon matrix 50 3~15μm; Or, in the nano-silicon deposited carbon matrix, the nano-silicon pore filling deposition rate is 35-90%, preferably 75-85%, more preferably 78-82%, and the pore volume is 0.05-0.80cm 3 / g, nano-silicon accounts for 20-70% by weight; Alternatively, the mass of the carbon deposited by the vapor phase carbon is 1 to 5% of the total mass of the final product.
6. The method for preparing the porous silicon-carbon negative electrode material according to claim 3, characterized in that: The process of preparing the porous carbon matrix is as follows: a first carbon source, a second carbon source and an inorganic salt are mixed and granulated to form a granular material, and then the granular material is sintered under an inert atmosphere; preferably, the granulation temperature is 150 to 250° C.; preferably, the sintering temperature is 300 to 500° C., preferably 440 to 460° C.; preferably, the sintering time is 1 to 3 hours; Alternatively, the process of nano-silicon deposition is: mixing a silicon source with an inert gas and performing vapor deposition at 300-600°C; preferably, the inert gas is selected from at least one of argon, neon, helium and nitrogen; preferably, the vapor deposition temperature is 430-470°C.
7. The method for preparing the porous silicon-carbon negative electrode material according to claim 3, characterized in that: The heat treatment temperature is 650-1000°C; preferably, the heat treatment time is 2-5h; Or, the acid mass concentration used for pickling is 1 to 15wt%; Alternatively, the temperature of the vapor phase carbon deposition is 400 to 900° C., and the time of the vapor phase carbon deposition is 1 to 3 hours.
8. Use of the porous silicon-carbon negative electrode material according to claim 1 or 2 or the porous silicon-carbon negative electrode material obtained by the preparation method according to any one of claims 3 to 7 in preparing negative electrode sheets.
9. The use according to claim 8, characterized in that: The negative electrode plate is composed of a current collector and an active layer attached to the surface of the current collector, and the active material in the active layer includes the porous silicon-carbon negative electrode material; preferably, the active material, the conductive agent, the binder, and the thickener are added to a solvent to form a slurry, and the slurry is placed on the surface of the current collector and dried to obtain the slurry; preferably, the active material also includes graphite; further preferably, the mass ratio of graphite to the porous silicon-carbon negative electrode material is 15.0-20.0:1, preferably 18.0-19.0:
1.
10. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The active material used in the negative electrode includes the porous silicon-carbon negative electrode material according to claim 1 or 2 or the porous silicon-carbon negative electrode material obtained by the preparation method according to any one of claims 3 to 7.